Teach for India : marketing an idea - Hennessy, Julie; Krishman, Charag ([London] : SAGE, 2016)
In 2008, Shaheen Mistri, founder of the nonprofit Teach For India (TFI), was grappling with applying and adapting the business and recruitment models of the successful U.S.-based Teach For America and UK-based Teach First to meet the challenges of the education sector in India. The case provides a review of the U.S.- and UK-based models, as well as an analysis of the factors that drove their growth in their respective markets.
Originally Published in: Hennessy, J., & Krishman, C. (2014). Teach For India: Marketing an Idea. 5-413-752. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on online resource; title from home page (viewed on May 3, 2016).
Keywords: elektronické knihy; electronic books; Non-governmental organizations -- Management -- Case studies; Non-governmental organizations -- Marketing -- Case studies; Branding (Marketing) -- Case studies